Post-traumatic stress disorder in patients with spinal-cord injuries. (June 2013) - Moodley, Nancy; Pillay, Basil J
The majority of spinal-cord injuries result from traumatic incidents such as motor vehicle accidents, falls, and acts of violence such as stab and gunshot wounds. Given the traumatic and life-threatening nature of most spinal-cord injuries, especially in a country like South Africa, where there is a high level of violent crime, post-traumatic stress disorder can be a common consequence for many patients. Using a prospective design, a total of 112 traumatic spinal-cord-injured patients, drawn from government hospitals in the Durban (South Africa) metropolitan and surrounding areas, were assessed. The control group consisted of 79 patients who had amputations. Post-traumatic stress disorder was assessed using the Impact of Event Scale–Revised and Post-Traumatic Diagnostic Scale. In addition, a semi-structured interview was conducted and supplementary data were obtained from each patient's file. The results indicated a high rate of post-traumatic stress disorder following traumatic spinal-cord injuries. Road traffic accidents were the most common cause of traumatic spinal-cord injuries. Single young males were found to be at greater risk of sustaining such injuries. The results and discussion emphasise the ubiquitous multicultural issues that influence outcomes. This study highlights the need for psychological intervention following traumatic spinal-cord injuries due to the high rate of post-traumatic stress disorder symptoms.